Role of allergy in the development of alopecia areata - A. A. Barilo; S. V. Smirnova (Медицинская иммунология, 2022)
Alopecia areata is an autoimmune disease characterized by non-scarring hair loss with preservation of the hair follicle. Hair loss in alopecia areata can be either focal with the appearance of clearly defined foci of alopecia, or diffuse or complete hair loss in any area of the skin where hair follicles are present. Data on the role of food allergy in the development of alopecia areata and the nature of the sensitization spectrum are extremely scarce. Objective: to study the features of the spectrum of sensitization to food and pollen (cross-reacting) allergens in patients with alopecia areata.The study involved patients with alopecia areata (n = 17), who were divided into groups according to age: group 1 — children (n = 9) and group 2 — adults (n = 8). All patients underwent a specific allergological examination: collection of an allergic history, skin prick testing with food and pollen allergens (Allergopharma, Germany).Analysis of the spectrum of sensitization to food allergens in patients with alopecia areata revealed features depending on their age. Thus, in the group of sick children, the highest frequency of sensitization to whole chicken eggs, food cereals, yeast, soybeans and cow's milk proteins was noted. In the group of sick adults, the most significant food allergens were: egg protein, rye flour, oats. Among the pollen allergens in the first group of patients, the most common allergens were a mixture of weed and grass pollen, in the second group, a mixture of meadow grass pollen. All patients, taking into account allergological testing, were administered an individual elimination diet with the exclusion of causally significant allergens, taking into account crossreacting allergens. The elimination effect was assessed 2 months after the start of the elimination diet. 70% of patients showed a clinical improvement, i.e., the growth of vellus was noted (vellus depigmented hair) in the foci of alopecia, as well as terminal pigmented hair. Complete regression of alopecia foci occurred on average within 3-6 months from the start of therapy.The sensitization to food and pollen (cross-reacting) allergens in patients with alopecia areata and the positive effect of the elimination diet revealed in our study well supports the role of food allergy in the development of this disorder. Therefore, the study of the causal relationship between food allergy and alopecia areata is of particular relevance and creates prerequisites for the discovery of new diagnostic and therapeutic options.